Methylnaltrexone for opioid-induced constipation: review and meta-analyses for objective plus subjective efficacy and safety outcomes - Siemens W; Becker G (Dove Medical Press, 2016)
Waldemar Siemens, Gerhild Becker Clinic for Palliative Care, Medical Center, University of Freiburg, Faculty of Medicine, University of Freiburg, Freiburg, Germany Introduction: Opioid-induced constipation (OIC) is a frequent adverse event that impairs patients’ quality of life. This article evaluates the objective plus subjective efficacy and the safety of methylnaltrexone (MNTX) in OIC patients.Methods: Randomized controlled trials from a recent systematic review were included. In addition, a PubMed search was conducted for January 2014 to December 21, 2015. We included randomized controlled trials with adult OIC patients, MNTX as study drug, and OIC as primary outcome. Results were categorized in three outcome types: objective outcome measures (eg, time to laxation), patient-reported outcomes (eg, straining), and global burden measures (eg, constipation distress). Dichotomous meta-analyses with risk ratios (RRs) and 95% confidence intervals (CIs) were calculated using RevMan 5.3. Only comparisons between MNTX and placebo were made.Results: We included seven studies with 1,860 patients. A meta-analysis revealed that patients under MNTX had considerably more rescue-free bowel movement within 4 hours after the first dose (RR 3.74, 95% CI 2.87 to 4.86; five studies, n=938; I2=0). Results of the review indicated that patients under MNTX had a higher stool frequency and needed less time to laxation compared with placebo. Moreover, patients receiving MNTX tended to have better values in patient-reported outcomes and global burden measures. Meta-analyses on safety revealed that patients under MNTX experienced more abdominal pain (RR 2.38, 95% CI 1.75 to 3.23; six studies, n=1,412; I2=60%) but showed a nonsignificant tendency in nausea (RR 1.27, 95% CI 0.90 to 1.78; six studies, n=1,412; I2=12%) and diarrhea (RR 1.45, 95% CI 0.94 to 2.24; five studies, n=1,258; I2=45%). The incidence of MNTX-related serious adverse events was 0.2% (4/1,860).Conclusion: MNTX has been shown to be effective and safe. Future randomized controlled trials should consequently incorporate objective outcome measures, patient-reported outcomes, and global burden measures, and research the efficacy of MNTX in other populations, for example, patients under opioids after surgical procedures. Keywords: opioid-induced constipation, methylnaltrexone, patient-reported outcomes, review, meta-analysis